Financial Distress Analysis of Companies Listed on the Indonesia Stock Exchange: Case Study of PT Waskita Karya, Tbk. Period 2020-2023 - Angreyani, Andi Dewi; Nasifa, Naurafatun; Ekawaty, Charisma; Rajab, Muh. Alwi; Putra, Muh. Al-Fatah Arief (Entrepreneurship, Management, and Business Research Journal, 2024)
Penelitian ini menggunakan teknik analisis kuantitatif. Hasil akhir penelitian ini menunjukkan bahwa kinerja keuangan PT. Waskita Karya, Tbk. Yang di analisis menggunakan metode Altman Z-Score periode 2020 – 2023 diklasifikasikan berada dalam kondisi distress zone atau dalam kondisi zona bangkrut. Hasil prediksi financial distress memakai metode Altman Z-Score pada PT. Waskita Karya, Tbk. mendapati perusahaan berada di zona bangkrut (distress zone) pada tahun 2023. This research uses quantitative analysis techniques. The final results of this study indicate that the financial performance of PT. Waskita Karya, Tbk. Which is analyzed using the Altman Z-Score method for the period 2020 - 2023 is classified as being in a distress zone or in a bankrupt zone condition. The results of predicting financial distress using the Altman Z-Score method at PT. Waskita Karya, Tbk. found that the company was in the distress zone in 2023.